HYPOGLYCEMIC ACTIVITY OF SOME INDONESIAN RICE VARIETIES AND THEIR PHYSICOCHEMICAL PROPERTIES - Widowati, Sri; Astawan, Made; Muchtadi, Deddy; Wresdiyati, Tutik (Indonesian Journal of Agricultural Science, 2006)
Diabetes mellitus is a spectrum of inherited and acquired disorderscharacterized by elevating blood glucose levels. Diabetesis an abnormal carbohydrate metabolism, therefore, diet therapyfor diabetics plays a key role in the management of thedisease. Most Indonesian people consume rice as source ofenergy and protein. Generally, diabetics consume very limitedrice because they believe that rice is the one of hyperglycemicfood, even though different rice varieties have large range ofglycemic index. The study aimed to evaluate hypoglycemicproperties by using rat assay and chemical characteristics of 10Indonesian rice varieties, i.e. Pandan Wangi, Rojolele, BengawanSolo, Cenana Bali, Memberamo, Celebes, Ciherang, BatangPiaman, Cisokan, and Lusi. Taj Mahal, an herbal ponni importedrice, was used as a comparison. Male Sprague Dawley rats (150-200 g body weight) were used for hypoglycemic assay. The ratswere fasted overnight before the blood glucose was measured inthe morning. The rats were then feed with 4.5 g rice per kgbody weight by oral administration, followed by 1 ml of 10%glucose solution in the next 30 minutes. The blood glucose wasmeasured for the next 30, 60, 90, and 120 minutes. Changes inblood glucose concentrations (mg dl-1) before and after the oraladministrations were calculated for each rice variety tested.Results showed that Cisokan and Batang Piaman were categorizedas low glycemic responses and Ciherang as high glycemic response,while the other varieties (Memberamo, Cenana Bali,Lusi, Bengawan Solo, Pandan Wangi, Celebes, and Rojo Lele)showed moderate glycemic responses. As the best hypoglycemicactivity, Cisokan contained high amylose (27.6%), fat (0.87%),total dietary fiber (6.24%), resistant starch (2.02%), and loweststarch digestibility (52.2%), which are ideal for diabeticâs consumption.Ciherang as the worst hypoglycemic activity had lowresistant starch (1.78%), low total dietary fiber (4.52%), and mediumamylose (23.0%). This study implies that Cisokan varietyis suitable for diabeticâs consumption.